Association of Researcher Characteristics and Entrepreneurial Intention (2024)
Investigating the antecedents and determinants of entrepreneurial intention is key to understanding the beginning of the entrepreneurial process. There is scarce literature on academic entrepreneurship that identifies the characteristics of an individual in an academic context with the intention of starting a spin-off company. This study explores the association of gender, age, research certification and knowledge area to Academic Entrepreneurial Intention. To this end, data was obtained from the participation of 172 academics at a Mexican university. Through logistic regression, it was possible to find a significant association between age, research certification and certain knowledge areas to academic entrepreneurial intention. This represents a first approximation to identifying the key factors that affect the academic entrepreneurship process, focused particularly on entrepreneurial intention.  JEL Codes: L26, M13 Received: 06/03/2024.  Accepted: 03/06/2024.  Published: 20/06/2024.